Electronic Lexicography: Traditional and Modern Approaches М. V. Маkarych1), Yu. B. Popova1), M. O. Shved2) - M. V. Маkarych; Yu. B. Popova; M. O. Shved (Наука и техника)
Nowadays there are a lot of modern technologies in electronic lexicography: speech synthesis technology, cross-referencing between dictionary modules, spell-checking functions, etc. The increasing availability of online information has necessitated intensive research in the area of automatic text summarization within the Natural Language Processing community. Belarusian scientists are also interested in this sphere and new lexicographical approaches for creating a linguistic database are shown in the paper. The authors present English-Belarusian-Russian electronic dictionary TechLex. This is the project of the 2nd English Department and the Department of Software for Information Systems and Technologies of the Belarusian National Technical University. The linguistic database of the dictionary is compiled not by the traditional method of processing a large number of paper dictionaries and combining the received translations, but by sequential processing of scientific and technical English-language periodicals. While the designing the dictionary the authors have taken into account the analysis of modern electronic multilingual translation dictionaries and created a client-server application in the Java programming language. The client part of the system contains a mobile application for the Android operating system, which has been tested on tablets and smartphones with different screen diagonals. The interface of the TechLex dictionary is designed taking into account the possibility of adding new subject areas and filling them with appropriate lexical material. The main advantage of our dictionary is that it is the first technical multilingual electronic dictionary having a Belarusian version.